1994
DOI: 10.1364/ol.19.001828
|View full text |Cite
|
Sign up to set email alerts
|

Second-harmonic generation in absorptive media

Abstract: The solution of the coupled-wave equations for second-harmonic generation in a near-resonant three-level system is extended to include absorption.It is shown, within second-order perturbation theory, that double resonance is the optimal conversion condition, despite absorption enhancement.We extend the solution numerically, using nonperturbative susceptibilities derived within the rotating-wave approximation, to saturating intensities and discuss the modifications to the perturbative conclusions as well as the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

1996
1996
2007
2007

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(2 citation statements)
references
References 11 publications
1
1
0
Order By: Relevance
“…These experiments were interpreted using the formalism of cavity polaritons (Savvidis 2001), and the configuration where the phase-matching was optimised was given the name of 'magic angle configuration'. However, the phase-matching phenomenon described by the authors is actually similar to a phenomenon which had previously been reported in another experiment, where the absorption in a quantum well had been used for controlling the index function (Almogy 1994). While there may not be any 'magic' involved in this phenomenon, it nonetheless finds its place among other phase matching phenomena (Baas 2004;Eastham 2003;Whittaker 2001).…”
Section: X(l) Photonic Crystals 249supporting
confidence: 81%
“…These experiments were interpreted using the formalism of cavity polaritons (Savvidis 2001), and the configuration where the phase-matching was optimised was given the name of 'magic angle configuration'. However, the phase-matching phenomenon described by the authors is actually similar to a phenomenon which had previously been reported in another experiment, where the absorption in a quantum well had been used for controlling the index function (Almogy 1994). While there may not be any 'magic' involved in this phenomenon, it nonetheless finds its place among other phase matching phenomena (Baas 2004;Eastham 2003;Whittaker 2001).…”
Section: X(l) Photonic Crystals 249supporting
confidence: 81%
“…Alternatively, they also reported an experimental observation of resonantly enhanced slow-light four-wave mixing in such cold Rb atomic media [16]. For three-level system, efficient second-harmonic generation in absorptive media was studied by Almogy and Yariv [20].…”
mentioning
confidence: 98%